Additive manufacturing of alloy and multi-metal oxide coated electrodes for electrolysis of water - Hegde, Chidanand (Nanyang Technological University, 2021)
The design of active catalysts and low-cost fabrication of electrodes are crucial to realize renewable hydrogen production from alkaline electrolysis. Herein, we attempted to (i) synthesize active catalysts based on earth-abundant Ni, (ii) develop an additive manufacturing process for rapid and low-cost fabrication of electrodes. Firstly, we report Cu, Fe co-doped Ni that shows remarkable activity for hydrogen evolution reaction. Doping of Cu and Fe improved the specific activity of Ni by 4 times and tuned the ΔGH of Ni from -0.258 eV to -0.131 eV. Secondly, we report NiAg0.4 heterogeneous alloy that shows Pt/C-like activity for hydrogen evolution. Experimental results accompanied by the theoretical calculations establish the role of the Ni-Ag interface in promoting hydrogen evolution. Finally, we report a novel femtosecond laser direct writing process to fabricate electrodes coated with multi-metal oxide and alloy nanoparticles. The fabricated electrodes show remarkable activity and durability for alkaline electrolysis.